Sweet potato (Ipomoea batatas L.) leaf polyphenols ameliorate hyperglycemia in type 2 diabetes mellitus mice. Issue 9 (16th April 2021) - Luo, Dan; Mu, Taihua; Sun, Hongnan
Abstract : The hypoglycemic effects and potential mechanism of sweet potato leaf polyphenols (SPLP) on type 2 diabetes mellitus (T2DM) were investigated. Abstract : The hypoglycemic effects and potential mechanism of sweet potato leaf polyphenols (SPLP) on type 2 diabetes mellitus (T2DM) were investigated. Results showed that oral administration of SPLP to mice could alleviate body weight loss, decrease fasting blood glucose levels (by 64.78%) and improve oral glucose tolerance compared with those of untreated diabetic mice. Furthermore, increased fasting serum insulin levels (by 100.11%), ameliorated insulin resistance and improved hepatic glycogen (by 126.78%) and muscle glycogen (increased by 135.85%) were observed in the SPLP treatment group. SPLP also could reverse dyslipidemia, as indicated by decreased total cholesterol, triglycerides, low density lipoprotein-cholesterol and promoted high density lipoprotein-cholesterol. Histopathological analysis revealed that SPLP could relieve liver inflammation and maintain the islet structure to inhibit β-cell apoptosis. A quantitative real-time polymerase chain reaction confirmed that SPLP could up-regulate the phosphatidylinositol 3-kinase/protein kinase B/glycogen synthase kinase-3β signaling pathway to improve glucose metabolism and up-regulate the phosphatidylinositol 3-kinase/protein kinase B/glucose transporter 4 signaling pathway in the skeletal muscle to enhance glucose transport. This study provides useful information to support the application of SPLP as a natural product for the treatment of T2DM.